Students Obstacles in Listening Comprehension in English Learning - Muhammad Hasyimsyah Batubara; Fatmawa Fatmawa (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
In developing a person's life, understanding various aspects of life comes from language learning. One aspect of language learning that plays a vital role is listening to conversations spoken by readers. This research has a qualitative descriptive pattern using selected literature reports for systematic reviews and meta-analysis methods. The source of the literature search was articles indexed on the DOAJ portal from 2016-2022, while the data collected was in the form of articles related to students' difficulties in learning to listen in EL. Document analysis techniques are used to solve data analysis problems. The results show that the factors that cause obstacles in learning listening are students' low attitudes and willingness to learn listening subjects, and the teacher's strategy in teaching the material also creates significant obstacles in students' abilities. Moreover, it is not overlooked that the recording media used also severely influences students' ability to capture verbal messages in listening activities.